2016
DOI: 10.1097/adt.0000000000000083
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Treatment Integrity in Alcohol Behavioral Couple Therapy

Abstract: Objectives Alcohol Behavioral Couple Therapy (ABCT) is an efficacious treatment for alcohol use disorders. Coding treatment integrity can shed light on the active ingredients of ABCT, but there are no published studies of treatment integrity instruments for ABCT. The present study describes the development and initial reliability of the Treatment Integrity Rating System – Couples Version (C-TIRS) for ABCT. Methods The C-TIRS was used to rate 284 first- and mid-treatment ABCT sessions of 188 couples in four r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Every therapy session was audio-taped and therapy integrity was assessed for a subset of these tapes via: (a) the Therapist Checklist, independent rater version, to code treatment components delivered in each session from 3 to 0 as thoroughly, moderately, minimally, or not covered. Average pairwise percent agreement within one point for the Therapist Checklist across 9 independent raters listening to audiotaped sessions, was 94%; and (b) the Treatment Integrity Rating System (TIRS, see Hallgren et al, 2016) created for this study, which included 39 five-point Likert scale items to assess domains common to both treatment conditions (e.g., general interventions, female-specific interventions, common factors) and unique to a single treatment condition (e.g., group therapy interventions). Across 9 raters, pairwise ICCs were .63 for the TIRS.…”
Section: Methodsmentioning
confidence: 99%
“…Every therapy session was audio-taped and therapy integrity was assessed for a subset of these tapes via: (a) the Therapist Checklist, independent rater version, to code treatment components delivered in each session from 3 to 0 as thoroughly, moderately, minimally, or not covered. Average pairwise percent agreement within one point for the Therapist Checklist across 9 independent raters listening to audiotaped sessions, was 94%; and (b) the Treatment Integrity Rating System (TIRS, see Hallgren et al, 2016) created for this study, which included 39 five-point Likert scale items to assess domains common to both treatment conditions (e.g., general interventions, female-specific interventions, common factors) and unique to a single treatment condition (e.g., group therapy interventions). Across 9 raters, pairwise ICCs were .63 for the TIRS.…”
Section: Methodsmentioning
confidence: 99%
“…Individual therapy sessions were 60 minutes; couple sessions were 90 minutes. Treatment fidelity was rated for a subset of first‐ and mid‐treatment sessions and indicated adequate treatment delivery .…”
Section: Methodsmentioning
confidence: 99%
“…When self‐monitoring cards were missing or incomplete, therapists were instructed to fill in this information with the clients through retrospective recall. Fidelity ratings indicated that cards were reviewed in 93.7% of the 79 mid‐treatment sessions available for rating .…”
Section: Methodsmentioning
confidence: 99%
“…Helpful resources for evaluating the fidelity of BCT delivery include the rating system by Hallgren et al. (2016), which has been used evaluate therapists’ delivery of the McCrady and Epstein (2009) protocol, and the rating system by O’Farrell (2013), which has been used to evaluate therapists’ delivery of the O’Farrell (2011) protocol.…”
Section: Training and Disseminationmentioning
confidence: 99%
“…Role play, it is important to note, has the advantage of being able to use standardized case scenarios for evaluation and eliminates concerns about potential breach of confidentiality in releasing session recordings of actual clients. Helpful resources for evaluating the fidelity of BCT delivery include the rating system by Hallgren et al (2016), which has been used evaluate therapists' delivery of the protocol, and the rating system by O'Farrell (2013), which has been used to evaluate therapists' delivery of the O'Farrell (2011) protocol.…”
Section: Training and Disseminationmentioning
confidence: 99%